OBSERVATIONS ON THE SEASONAL FLUCTUATIONS OF PLANKTON IN THE CHILKA LAKE - Patnaik, S (Indian Journal of Fisheries, 2011)
This paper gives an account of the main features of the plankton of f-e ChilicaLake from April, 1964 to March, 1965. The seasonal fluctuations of the main constituentgroups of phytoplankton and zooplankton in relation to some of Jthe environmentalvariables have been discussed. The diatoms and copepods formed the dominant groupsin the plankton during the above period.